A survey on the use of "Oh My English" program in ESL lessons: perspectives of SMK (P) Sultan Abu Bakar, Muar ESL learners./ Muhammad Arddri Ghazali - Ghazali, Muhammad Arddri (Faculty of Education, 2014)
"Oh My English" program gives such a huge impact to the audience especially in Malaysia. Awarded "The Best Comedy Kids TV Series" in Anugerah Lawak Warna and was nominated as Top 5 in "Favourite Drama TV Show" for "Astro On the Go Fan Choice Awards", its effectiveness cannot be argued. Besides that, the snippets of the show have had almost one million YouTube views and the sitcom had garnered 50,000 Facebook fans and the informal teaching methods employed by the media to help students with English are affirmed were often more effective than the formal methods employed in schools. Hence, with all of these compliments and support from the society, the intention to investigate more on the discernment of using "Oh My English" program in English lesson from ESL learners should be carried out, so that, its effectiveness towards the students will be proven. Therefore, a quantitative study was conducted to investigate whether students of SMK Sultan Abu Bakar, Muar, Johor prefer "Oh My English" program to be used in English lessons as well as to identify how "Oh My English" program motivates students in learning English language and to examine the suitability of the "Oh My English" program in term of its program features, contents and practicality. The findings have let to interesting discussion that the students of SMK Sultan Abu Bakar, Muar, Johor prefer "Oh My English" program to be used in English lesson, the program motivates the students in several ways and it is proven that the program of "Oh My English" is suitable in term of its program features, content and practicality. Last but not least, suggestions for further research are discussed and provided.